Comparison of efficacy and safety of topical luliconazole with topical fluconazole against tinea corporis in a tertiary care hospital - Seshathri, E.; Krishna, R. Deepthi (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Dermatophytosis is a common cutaneous infection worldwide with prevalence varying from 20% to 25%. Luliconazole is a newer topical antifungal applied once daily with greater reservoir property in stratum corneum. Objective of the study was to compare the clinical efficacy and safety of luliconazole 1% cream with Fluconazole 1% cream in patients with mild to severe grades of tinea corporis. Methods: A total of 100 patients with mycologically confirmed tinea corporis were randomised into group A and B respectively. Group A, 50 patients received luliconazole 1% for 2 weeks and group B, 50 patients received fluconazole 1% cream for 4 weeks. Patients were clinically and mycologically evaluated on 0, 2nd and 4th week of treatment and followed up on 8th week for any relapse. Results: Significant improvement in efficacy was seen in Luliconazole while compared with fluconazole group against tinea corporis infection. Mycological cure and clinical improvement showed significant difference in group A. The safety and tolerability profile of both groups were good and statistically comparable. Conclusions: Luliconazole 1% cream is found to be safe, effective and tolerable with low incidence of relapse than fluconazole 1% cream.